Mechanisms of mesothelial cell response to viral infections: HDAC1-3 inhibition blocks poly(I:C)-induced type I interferon response and modulates the mesenchymal/inflammatory phenotype - Trionfetti, Flavia; Montaldo, Claudia; Caiello, Ivan; Bontempi, Giulio; Terri, Michela; Tiberi, Marta; Marchant, Vanessa; Domenici, Alessandro; Menè, Paolo; Cordani, Marco; Zwergel, Clemens; Prencipe, Giusi; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Infectious peritonitis is a leading cause of peritoneal functional impairment and a primary factor for therapy discontinuation in peritoneal dialysis (PD) patients. Although bacterial infections are a common cause of peritonitis episodes, emerging evidence suggests a role for viral pathogens. Toll-like receptors (TLRs) specifically recognize conserved pathogen-associated molecular patterns (PAMPs) from bacteria, viruses, and fungi, thereby orchestrating the ensuing inflammatory/immune responses. Among TLRs, TLR3 recognizes viral dsRNA and triggers antiviral response cascades upon activation. Epigenetic regulation, mediated by histone deacetylase (HDAC), has been demonstrated to control several cellular functions in response to various extracellular stimuli. Employing epigenetic target modulators, such as epidrugs, is a current therapeutic option in several cancers and holds promise in treating viral diseases. This study aims to elucidate the impact of TLR3 stimulation on the plasticity of human mesothelial cells (MCs) in PD patients and to investigate the effects of HDAC1-3 inhibition. Treatment of MCs from PD patients with the TLR3 agonist polyinosinic:polycytidylic acid (Poly(I:C)), led to the acquisition of a bona fide mesothelial-to-mesenchymal transition (MMT) characterized by the upregulation of mesenchymal genes and loss of epithelial-like features. Moreover, Poly(I:C) modulated the expression of several inflammatory cytokines and chemokines. A quantitative proteomic analysis of MCs treated with MS-275, an HDAC1-3 inhibitor, unveiled altered expression of several proteins, including inflammatory cytokines/chemokines and interferon-stimulated genes (ISGs). Treatment with MS-275 facilitated MMT reversal and inhibited the interferon signature, which was associated with reduced STAT1 phosphorylation. However, the modulation of inflammatory cytokine/chemokine production was not univocal, as IL-6 and CXCL8 were augmented while TNF-α and CXCL10 were decreased. Collectively, our findings underline the significance of viral infections in acquiring a mesenchymal-like phenotype by MCs and the potential consequences of virus-associated peritonitis episodes for PD patients. The observed promotion of MMT reversal and interferon response inhibition by an HDAC1-3 inhibitor, albeit without a general impact on inflammatory cytokine production, has translational implications deserving further analysis.